KAJIAN ETNOMATEMATIKA PADA CANDI BAHAL DI KABUPATEN PADANG LAWAS UTARA - Hendri Muliadi; Suparni Suparni (JURNAL MathEdu (Mathematic Education Journal), 2026)
Bahal Temple is a Vajrayana Buddhist temple complex located in Bahal Village, Padang Bolak District, North Padang Lawas Regency, North Sumatra Province. This temple complex consists of three main buildings, namely Biaro Bahal I, Biaro Bahal II, and Biaro Bahal III, which are arranged in a straight line and constructed using red bricks. In addition to its high historical and cultural value, Bahal Temple also contains various mathematical concepts that can be studied through an ethnomathematical approach. This study aims to identify and describe the mathematical concepts embedded in the structure and ornaments of Bahal Temple and to analyze its potential as a source of contextual mathematics learning at the junior and senior high school levels. The research method used is a qualitative study with a descriptive-ethnographic approach through observation, documentation, and literature review. The results show that Bahal Temple contains concepts of solid geometry, symmetry, repeating patterns, as well as ratio and proportion. These findings indicate that Bahal Temple has great potential as a meaningful and contextual source of ethnomathematics learning